Perancangan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di PT. X Berdasarkan Peraturan Pemerintah (PP) Nomor 50 Tahun 2012 - Clarissa Nathania Irawan; Kriswanto Widiawan (Jurnal Titra, 2023)
In 2022, PT. X recorded about 25 work accidents. All control efforts have been made, but work accidents still continue to occur so that PT. X continues to experience losses. This is because the company hasn’t had SMK3 yet. Therefore, based on the problem, the SMK3 design will immediately carried out. In this research, SMK3 was designed based on Government Regulation Number 50 of 2012 which can be applied and ind accordance with the company’s capabilities. The SMK3 design method includes interviews, observation, initial audit, OSHimplementation design, SMK3 dissemination, and final audit. The design will be carried out until the advanced stage, namely 166 sub-criteria with the exception of clause 11 and clause 5.4 (5.4.2) so that the number of sub-criteria to be fulfilled is 162 sub-criteria. On the results of the initial audit, PT. X only met 35,8% (58 of 162 sub-criteria). Therefore, a design is carried out such asmaking K3 policies, OSH terms and conditions, work procedures, and forms. After designing, the final audit results obtained are 61,1% (99 of 162 sub-criteria). However, if the company succeeds in carrying out and implementing the design, it will obtain a final audit result of 100% (162 sub-criteria).